Carotenoids: diversification in Malaysian traditional vegetables (ulam) and medicinal species - Mohd Zaifuddin, Fatimah Azzahra; Othman, Rashidi; Mohd Hassan, Norazian (2013)
Vitamin A deficiency (VAD) is one of the continuous leading causes of children and pregnant women death. To overcome this malnutrition which currently affected one-third of the world population, there is always renewed interest in exploring numerous dietary sources rich in carotenoids which some of them serve as pre-cursors to vitamin A (pro-vitamin A). Therefore, this study was aimed to explore various dietary sources for carotenoids in 28 ulam and medicinal species which are commonly consumed by the local folks. HPLC analysis employed in this study has resulted in determination and quantification of seven types of carotenoids in the food matrices; neoxanthin, violaxanthin, lutein, zeaxanthin, β-cryptoxanthin, β-carotene and β-carotene. Interestingly, these carotenoids were found in varying concentration. Total carotenoids content quantified in all of the samples lies between 1.315 ± 0.007 to 190.301 ± 3.427 mg/g DW where cekur manis has the highest content. The total vitamin A activity (in terms of retinol equivalent, RE) of every species is also included in this study. The results suggested that at least 20 of the ulam and medicinal species may be used as alternative food intervention to eliminate VAD as a public health concern.